The Steps to Master Listening Skills through the Use of the Independent Dimension-Based Listen English Daily Practice Application Through the Pancasila Student Profile Scheme - Prihatini, Candraning; Musiman, Musiman; Fitriyani , Dhafiya (ELT-Lectura, 2025)
This research aims to describe the implementation of effective steps to master listening skills through the use of the Independent Dimension-based Listen English Daily Practice application through the Pancasila student profile scheme. In the English Language Education study program at Muhammadiyah University of Lampung, the Listen English Daily application is used to teach listening comprehension. This shows the effective use of the pre-listening, while-listening, and post-listening stages. This application not only helps students improve their listening skills but also receives positive responses from students thanks to its familiar topics, interesting features, and ease of use. This research uses descriptive analysis and focuses on the Listen English Daily Practice application as the subject. The focus of the research is how this application can be used to help Pancasila students learn to listen better. The results of the study show that using the Listen English Daily Practice application can maximize English learning. This application helps improve language skills such as reading, writing, listening and speaking. Apart from that, this application supports the values ​​of the Pancasila student profile, namely being independent, critical, creative, working together and having global diversity. Therefore, this application not only improves speaking skills but also develops character in accordance with Pancasila values.